A carbon nanotubes composite filter for removal of oil particles. (14th November 2018) - Xu, Chengwei; Xie, Wenxia; Yu, Yan; Zhang, Jun; Yang, Jiangang
Abstract: Conventional fiber filters for oil particle filtration have inadequate efficiency and exorbitant increase of pressure drop. Carbon nanotubes (CNTs) with nanoscale diameter have the potential in cooking fume filtration field. In this work, we synthesized the CNTs-filter through CVD method to grow CNTs on the Al2 O3 -modified porous nickel foam substrate. We found that the CNTs-filter has high water repellency and outstanding oil-wetting property. Compared with the commercial glass fiber filter, the CNTs-filter has excellent filtration performance and lower pressure drop on the saturation stage for liquid oil aerosol. The filtration efficiency of CNTs-filter was higher than the HEPA filter standard. The pressure drop of saturation state was only 2 times higher than that of initial state, which is far less than glass fiber filter. In addition, the quality factor at saturation stage was improved due to the decrease of the raise ratio of pressure drop.